2011
DOI: 10.1002/hep.24686
|View full text |Cite
|
Sign up to set email alerts
|

CD59 incorporation protects hepatitis C virus against complement-mediated destruction

Abstract: Several enveloped viruses including HIV-1, CMV, HSV-1, Ebola virus, vaccinia virus, and influenza virus have been found to incorporate host regulators of complement activation (RCA) into their viral envelopes and, as a result, escape antibody-dependent complement-mediated lysis (ADCML). HCV is an enveloped virus of the family Flaviviridae and incorporates more than 10 host lipoproteins. Patients chronically infected with HCV develop high-titer and cross-reactive neutralizing antibodies (nAbs) yet fail to clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…In contrast, the acquired overexpression of CD59 confers resistance to complement-mediated cytolysis in cells infected with hepatitis B virus (9), hepatitis C virus (34), and human immunodeficiency virus (35), contributing to the occurrence of persistent infections. Furthermore, chronic inflammation, especially when induced by pathogens, has been implicated in tumorigenesis, where many proinflammatory and pathogenic virulence factors are produced in local tumor sites (36).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the acquired overexpression of CD59 confers resistance to complement-mediated cytolysis in cells infected with hepatitis B virus (9), hepatitis C virus (34), and human immunodeficiency virus (35), contributing to the occurrence of persistent infections. Furthermore, chronic inflammation, especially when induced by pathogens, has been implicated in tumorigenesis, where many proinflammatory and pathogenic virulence factors are produced in local tumor sites (36).…”
Section: Discussionmentioning
confidence: 99%
“…HCV incorporates CD59 into the viral lipid bilayer at biologically functional levels (17) and protects against antibody-dependent complement-mediated lysis. Thus, it is difficult to examine the role of CD55 in maintaining cell viability related to complement attack by depleting it alone in cells supporting HCV growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that incorporation of the complement-regulatory protein CD59 in HCV in plasma as well as proteins derived from cell lines (17) protected HCV from antibody-dependent complement-mediated lysis. Analogously, HBV X protein has been implicated in increasing expression of CD59 in hepatoma cell lines.…”
mentioning
confidence: 99%
“…The ER also plays a critical part in the synthesis and modification of glycosylphosphatidylinositol-anchored proteins (GPI-Aps) such as CD55 and CD59 in eukaryotic cells. Thus, it is possible for HCV to encounter and obtain CD55 or CD59 in the ER and other cellular organelles (23). Therefore, working with a susceptible model was necessary to determine the qualitative nature of the complement in chronically HCV-infected patient sera.…”
Section: Downregulation Of C9 In Hcv-infected Patient Samplesmentioning
confidence: 99%